The Effect of Compensation and Empowerment on Employee Loyalty Mediated by Job Satisfaction (Case Study at PT Permodalan Nasional Madani Regional Surabaya 1) - Mohamad Januar Bagus Indranata; Siti Safaria (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the effect of compensation and empowerment on employee loyalty with job satisfaction as an intervening variable. The research was conducted through survey with quantitative research type. Sampling was selected randomly with 100 PNM employees as respondents. This research use Partial Least Square (PLS) to test the hypothesis. This research found that compensation and empowerment have a significant effect on employee’s job satisfaction, compensation and empowerment do not have a significant effect on employee loyalty, and job satisfaction is able to mediate a relationship between compensation and empowerment on employee loyalty significantly